Case report: Unusual episodic myopathy in a patient with novel homozygous deletion of first coding exon of MICU1 gene - Sharova, Margarita; Skoblov, Mikhail; Dadali, Elena; Demina, Nina; Shchagina, Olga; Konovalov, Fedor; Ampleeva, Maria; Sharkova, Inna; Kutsev, Sergey (Frontiers in Neurology, 2022)
We present a patient with unusual episodes of muscular weakness due to homozygous deletion of exon 2 in MICU1 gene. 43 patients from 33 families were previously described with homozygous and compound heterozygous, predominantly Loss of Function (LoF) variants in the MICU1 gene that lead to autosomal recessive myopathy with extrapyramidal signs. Most described patients developed muscle weakness and elevated CK levels, and half of the patients had progressive extrapyramidal signs and learning disabilities. Our patient had a few severe acute episodes of muscle weakness with minimal myopathy features between episodes and a strongly elevated Creatinine Kinase (CK). WES was performed and the homozygous deletion of exon 2 was suspected. To validate the diagnosis, we performed an RNA analysis of all family members. To investigate the possible impact of this deletion on the phenotype we predicted a new Kozak sequence in exon 4 that could lead to the formation of a truncated MICU1 protein that could partly interact with MCU protein in a mitochondrial Ca2+ complex. We suspect that this unusual phenotype of the proband with MICU1-related myopathy could be explained by the presence of the truncated but partly functional protein. This work helps to define the clinical polymorphism of MICU1 deficiency better.